Strategies Of The Tiktok Account @kafani.id In Strengthening Brand Identity And Brand Awareness - Denisa, Alya; Tita Melia Milyane; Reni Nuraeni (PT ARRUS Intelektual Indonesia, 2024)
Abstract This study examines the marketing strategies employed by the TikTok account @kafani.id to strengthen its brand identity and build brand awareness within Indonesia’s rapidly growing TikTok user base. Using Kapferer’s Hexagonal Identity Prism framework, the research explores how @kafani.id creatively integrates elements like visual identity, brand personality, cultural values, and audience engagement to promote niche products such as burial shrouds and funeral supplies. Through a qualitative case study approach involving content analysis of TikTok activities, including live streaming sessions and audience interactions, the findings reveal that @kafani.id effectively leverages TikTok’s algorithm-driven promotion, viral marketing through electronic word-of-mouth (eWOM), and entertaining yet respectful communication. By combining educational and humorous content with active engagement, the brand creates a unique identity while fostering strong emotional connections with its audience. The study concludes that creativity, authenticity, and culturally driven narratives can transform unconventional products into appealing digital brands, emphasizing TikTok's potential as a powerful marketing platform.